Preface: 5th Asia Conference on Geological Research and Environmental Technology (GRET 2024) - Melville, Renata; Yu, Lin (Transactions on Environment, Energy and Earth Sciences, 2024)
The organizing committees are honored to present the proceedings of the 2024 5th Asia Conference on Geological Research and Environmental Technology (GRET 2024), held in Kamakura, Japan during October 26-27, 2024. GRET 2024 aims to bring together outstanding scholars, researchers, and students to exchange and share their experiences and research results about all aspects of earth science, geological research, natural resources, energy engineering, and environmental technology. We also provide the keynote address and several plenary invited speeches for the discussion of most recent innovations, trends, concerns, practical challenges encountered, and the various solutions. In everyone’s efforts, GRET 2024 was successfully held as scheduled. The conference model was divided into two parts, including keynote speeches and discussions. In the first part, keynote presentations were delivered in 30 minutes for each talk. The second part was held lasted nearly an hour in a communication group for experts and scholars to discuss more about the talks and presentations. We do believe your great participation will make our conference success and we would appreciate your participation. Hopefully, all participants and other interested readers will benefit or find inspirations from this proceeding. With our best regards, GRET 2024 Conference Organizing Kamakura, Japan